2015
DOI: 10.15616/bsl.2015.21.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Der p 2 with Toll-like Receptor 4 and its Effect on Cytokine Secretion

Abstract: Der p 2, which is a major allergen of house dust mite, plays an important role in the pathogenesis of allergic disease. There is controversy regarding whether Der p 2 binds to Toll-like receptor 4 (TLR4), and its inflammatory effect has not yet been elucidated. In the current study, we examined the interaction of Der p 2 with TLR4 and the effect of Der p 2 on cytokine release in THP-1 cells and lymphocytes. Among house dust mite extracts, recombinant TLR4 protein interacted with Der p 2. The overall structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Additionally, HDM increased TLR 4-mediated infiltration of eosinophils and neutrophils into the lungs of mice [ 47 ]. The HDM allergen Derp 2 activated TLR4 and induced IL-6, IL-8, and MCP-1 in THP-1 cells and lymphocytes [ 48 ]. These studies demonstrate the relationship between TLR4 and cytokine expression in HDM-stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HDM increased TLR 4-mediated infiltration of eosinophils and neutrophils into the lungs of mice [ 47 ]. The HDM allergen Derp 2 activated TLR4 and induced IL-6, IL-8, and MCP-1 in THP-1 cells and lymphocytes [ 48 ]. These studies demonstrate the relationship between TLR4 and cytokine expression in HDM-stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune pathways activation by non-protease allergens has been an important advance in allergen characterization. The first report showing this type of mechanism was the ability of Der p 2 to activate pro-inflammatory signals through TLR-4 in bronchial epithelial cells (17), a report followed by other effects of this allergen (18)(19)(20)(21)(22). Among other HDM allergens that can induce non-IgE mediated proinflammatory activation of bronchial epithelium are Der p 5 (23), Der p 13 (24), and Blo t 7 (25).…”
Section: Advances In Allergen Characterizationmentioning
confidence: 99%
“…The cell response to Der p 2 triggers the activation of the NF-κB and MAPK signaling pathways, which regulate the synthesis of inflammation intermediators in different manners [ 34 ]. Model studies on THP-1 cell cultures [ 3 ], as well as on isolated neutrophils and B-lymphocytes [ 12 ], showed that Der p 2 effectively promotes isolated cells to produce IL-6, IL-1, IL-8, CXCL10, and TNF-α. The isolated B-cells of blood also react to the allergen Der p 2 via the production of pro-inflammatory cytokines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on transfected HEK MD-2293FT cells showed that, similar to LPS, Der p 2 is able to induce the dimerization of TLR4 and the activation of intracellular signaling pathways, leading to the synthesis of pro-inflammatory cytokines and chemokines, and it can increase LPS-induced TLR4-dependent responses [ 3 ]. Der p 2 causes the elevated secretion of IL-6 and IL-8 cytokines by THP-1 monocytes and B-lymphocytes via the activation of TLR4 and MAPK [ 12 ]. LPS and Der p 2 demonstrated synergistic effects on IL-8 and IL-6 produced by BEAS2B lung cell lines.…”
Section: Introductionmentioning
confidence: 99%